DIALEKTIKA NORMA HUKUM ISLAM DAN ADAT-BUDAYA DALAM PARADIGMA ULAMA NAHDLATUL ULAMA: KAJIAN TIPOLOGIS - Dahlan, Moh (JURNAL ISLAM NUSANTARA, 2019)
The dialectic of Islamic legal norms and cultural customs often cause problems. Therefore, a relevant ijtihad (independent reasoning) is considerably required. By using a library research approach, the Nurcholish Madjid’s inclusive paradigm, and triangulation as a technique to collect the data, this study shows that the dialectic of Islamic legal norms and cultural customs has given rise to three typologies of inclusive Islamic legal thought; Firstly, Nadirsyah Hosen who has Islamic legal thoughts rejects absolutism-exclusiveism; Secondly, KH A Wahid Hasyim and KH Ahmad Ishomuddin who have a paradigm of Islamic (legal) thought see positively to religious plurality, Thirdly, the thoughts of KH Abdurrahman Wahid and KH Said Aqil Siradj who have Islamic legal thought stand for universal humanitarian values.